Measuring the effects of remifentanil on cerebral blood flow and arterial arrival time using 3D GRASE MRI with pulsed arterial spin labelling. - MacIntosh, B; Pattinson, K; Gallichan, D; Ahmad, I; Miller, K; Feinberg, D; Wise, R; Jezzard, P (2008)
Arterial spin labelling (ASL) has proved to be a promising magnetic resonance imaging (MRI) technique to measure brain perfusion. In this study, volumetric three-dimensional (3D) gradient and spin echo (GRASE) ASL was used to produce cerebral blood flow (CBF) and arterial arrival time (AAT) maps during rest and during an infusion of remifentanil. Gradient and spin echo ASL perfusion-weighted images were collected at multiple inflow times (500 to 2,500 ms in increments of 250 ms) to accurately fit an ASL perfusion model. Fit estimates were assessed using z-statistics, allowing voxels with a poor fit to be excluded from subsequent analyses. Nonparametric permutation testing showed voxels with a significant difference in CBF and AAT between conditions across a group of healthy participants (N=10). Administration of remifentanil produced an increase in end-tidal CO(2), an increase in CBF from 57+/-12.0 to 77+/-18.4 mL/100 g tissue per min and a reduction in AAT from 0.73+/-0.073 to 0.64+/-0.076 sec. Within grey matter, remifentanil produced a cerebrovascular response of 5.7+/-1.60 %CBF per mm Hg. Significant differences between physiologic conditions were observed in both CBF and AAT maps, indicating that 3D GRASE-ASL has the sensitivity to study changes in physiology at a voxel level.